A comparison of the stress hyperglycemia ratio, glycemic gap, and glucose to assess the impact of stress‐induced hyperglycemia on ischemic stroke outcome. Issue 12 (29th September 2021) - Roberts, Gregory; Sires, James; Chen, Angela; Thynne, Tilenka; Sullivan, Cheyne; Quinn, Stephen; Chen, Won Sun; Meyer, Emily
Abstract: Background: The aim of this study is to compare metrics specific for stress‐induced hyperglycemia (SIH) with glucose for predicting ischemic stroke outcome. Methods: This observational retrospective study (n = 300) included patients acutely hospitalized for ischemic stroke over a 3.8‐year period. We assessed the association between acute ischemic stroke outcome with the stress hyperglycemia ratio (SHR, relative increase in glycemia) and glycemic gap (GG, absolute increase in glycemia) using admission values and 5‐day maximum values, along with incidence of poor outcome above recognized clinical thresholds of glucose 10 mmol/L, SHR 1.14, and GG 2.5 mmol/L. Results: At admission, only SHR was associated with outcome after adjustment for clinical covariates (odds ratio [OR] = 2.88; 95% CI: 1.05‐7.91; P = .041), while glucose or GG were not. Admission SHR ≥ 1.14 was also an indicator of poor outcome (39.1% vs 23.4%, P = .016), but not glucose ≥10 mmol/L or GG ≥ 2.5 mmol/L. All 5‐day maximum glucose metrics were associated with outcome, as was any SHR ≥ 1.14 (40.9% vs 20.1%, P < .001) or GG ≥ 2.5 mmol/L (42.9% vs 23.4%, P = .011), but not glucose ≥10 mmol/L. Increased comorbidity was strongly associated with worse outcome ( P < .001) in all models. Conclusions: SHR provided the best prognostic insight at admission to assess the relationship between SIH and ischemic stroke outcome. Absolute glucose levels failed to account for natural interpatient variation in background glycemia and provided little prognostic insight. To assess the impact of SIH, future interventional studies need to be designed using designated markers of SIH such as SHR in preference to absolute glucose. Abstract : Highlights The impact of stress‐induced hyperglycemia on outcome is poorly reflected by absolute glucose levels. The stress hyperglycemia ratio (SHR) biomarker discriminates between interpatient variation in normal premorbid background glycemia related to glycosylated hemoglobin and the acute relative increase in glucose related to physiological stress that truly represents stress‐induced hyperglycemia. SHR at admission was superior to glucose in predicting ischemic stroke outcome. There is a need for interventional studies based on SHR rather than glucose to best assess management of stress‐induced hyperglycemia. 摘要: 背景: 本研究的目的是比较应激性高血糖(SIH)特异性指标相对于葡萄糖来预测缺血性卒中结局的效果。 方法: 这项观察回顾性研究(n=300)涵盖了在3.8年间因缺血性中风而急诊住院的患者。我们使用入院值和5天最大值评估急性缺血性卒中预后与应激性高血糖比率(SHR, 血糖相对升高)和血糖间隙(GG, 血糖绝对升高)之间的关系, 以及超过临床阈值葡萄糖10 mmol/L, SHR 1.14和GG 2.5 mmol/L的不良预后发生率。 结果: 入院时, 经临床协变量校正后, 只有自发性高血压与预后相关(优势比[OR]=2.88, 95%CI:1.05 7.91, P=0.041), 而葡萄糖或GG不是。入院SHR≥1.14也是预后不良的指标(39.1%vs 23.4%, P=0.016), 葡萄糖≥10 mmol/L或GG≥2.5 mmol/L则不是。所有5天最高血糖以及SHR≥1.14(40.9%vs 20.1%, P<.001)或GG≥2.5 mmol/L(42.9%vs 23.4%, P=0.011)都与预后相关, 葡萄糖≥10 mmol/L则不是。在所有模型中, 合并症增加与较差的预后密切相关(P<0.001)。 结论: SHR在入院时提供了很好的预后判断来评估自发性高血压与缺血性卒中预后的关系。绝对血糖水平不能解释患者间背景血糖的自然变化, 也不能提供对预后的判断。为了评估自发性高血压的影响, 未来的干预性研究需要使用自发性高血压的特定标记物, 如SHR, 而不是绝对葡萄糖值。